2018
DOI: 10.1021/acs.jmedchem.7b01925
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Exploration around 4-Aminoquinolines Chemical Space to Navigate the Lysine Methyltransferase G9a and DNA Methyltransferase Biological Spaces

Abstract: Epigenetic regulators that exhibit aberrant enzymatic activities or expression profiles are potential therapeutic targets for cancers. Specifically, enzymes responsible for methylation at histone-3 lysine-9 (like G9a) and aberrant DNA hypermethylation (DNMTs) have been implicated in a number of cancers. Recently, molecules bearing a 4-aminoquinoline scaffold were reported as dual inhibitors of these targets and showed a significant in vivo efficacy in animal models of hematological malignancies. Here, we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(71 citation statements)
references
References 22 publications
5
66
0
Order By: Relevance
“…The synthesis and biological activity of the three proprietary compounds CM-272, CM-679 and CM-986 has been reported [ 36 39 ]. Chemical structures and IC 50 values against EHMT2 (G9a) and DNMT1 are given in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis and biological activity of the three proprietary compounds CM-272, CM-679 and CM-986 has been reported [ 36 39 ]. Chemical structures and IC 50 values against EHMT2 (G9a) and DNMT1 are given in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, Rabal et al decided to design and synthetize a quinoline analog of UNC0638 98 , compound 100 (Figure ), to be tested against both DNMT1 and G9a through time‐resolved fluorescence resonance energy transfer (TR‐FRET) technique. Competition experiments confirmed that 100 displayed substrate‐competitive inhibition of both targets, with global reduction in H3K9me2 and 5‐methylcytosine (5mC) levels . Unfortunately, 100 did not show any antiproliferative response against ALL CEMO‐1 (GI 50 > 10 µM), DCLBL OCI‐Ly3 and OCI‐Ly10 (0% inhibition at 1 µM) and AML MV4‐11 (GI 50 > 10 µM) cell lines.…”
Section: The Mtdl Approachmentioning
confidence: 96%
“…367 and 5-methylcytosine (5mC) levels. 372,373 Unfortunately, 100 did not show any antiproliferative response against ALL CEMO-1 (GI 50 > 10 µM), DCLBL OCI-Ly3 and OCI-Ly10 (0% inhibition at 1 µM) and AML MV4-11…”
Section: Proteolysis Targeting Chimera Approach Applied To Epigenetmentioning
confidence: 98%
“…Based on studies that describe the interactions involved in the molecular recognition of G9a and DNMT1 [1,18,19]. Compound 6 (not present on the PDBs structures reported) was used to guide the development of a protocol that captured the interactions reported for other active compounds.…”
Section: Search For Ideal Conditionsmentioning
confidence: 99%
“…The work published by Rabal, et al (2018) is a key step forward in this analysis. They synthesized a novel series of 4-aminoquinolines as inhibitors of the enzymes lysine methyltransferase (G9a) and DNA methyltransferase 1 (DNMT1).…”
Section: Introductionmentioning
confidence: 99%